2011
DOI: 10.1007/s00213-010-2132-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 18-methoxycoronaridine on ghrelin-induced increases in sucrose intake and accumbal dopamine overflow in female rats

Abstract: Rationale 18-Methoxycoronaridine (18-MC), a selective antagonist of α3β4 nicotinic receptors, has been previously shown, in rats, to reduce the self-administration of several drugs of abuse, reduce operant responding for sucrose, and prevent the development of sucrose-induced obesity. It has become increasingly apparent that there is a significant overlap between the systems regulating drug reward and food intake, therefore, we investigated whether 18-MC might modulate the effects of ghrelin, one of several or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Further, peripheral administration of ghrelin increased the intake and preference of sucrose in rats. Supportively, it was recently shown that ghrelin (administered centrally as well as peripherally) increases whereas GHS-R1A antagonism suppresses the motivation to consume sucrose [37] and that central grelin administration increase the intake of sucrose in rats [38]. Given that the orexigenic peptide, ghrelin, regulates energy balance [8], the reduced sucrose intake may be related to its caloric content.…”
Section: Discussionmentioning
confidence: 97%
“…Further, peripheral administration of ghrelin increased the intake and preference of sucrose in rats. Supportively, it was recently shown that ghrelin (administered centrally as well as peripherally) increases whereas GHS-R1A antagonism suppresses the motivation to consume sucrose [37] and that central grelin administration increase the intake of sucrose in rats [38]. Given that the orexigenic peptide, ghrelin, regulates energy balance [8], the reduced sucrose intake may be related to its caloric content.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of behavior, it is clear that ghrelin alters the rewarding properties associated with food and drug reinforcers (Perello et al, 2010, Jerlhag et al, 2009, 2010, McCallum et al, 2011, Skibicka 2011, 2012). For example, ghrelin administration enhances the rewarding properties of high fat diet while ghrelin receptor antagonists abolish this effect (Perello et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work implicates a necessity for ghrelin signaling in a variety of rewarding behaviors including food, alcohol and psychostimulant reinforcement (Perello et al, 2010, Jerlhag et al, 2009, 2010, McCallum et al, 2011, Skibicka 2011, 2012). The mechanism of ghrelin action in the context of reward behavior likely occurs through activation of the ghrelin receptor (GHSR) (Jerlhag et al, 2009) within tegmental and cholinergic signaling systems which activate brain reward circuitry (Jerlhag et al, 2006, 2007, Skibicka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma acylated-ghrelin level was positively correlated with carbohydrate consumption, while inversely correlated with fat intake in rat (Beck et al 2002). Peripheral and central acylated-ghrelin injection stimulated dopamine release in NAc, accompanied by increased sucrose consumption (Landgren et al 2011, McCallum et al 2011. In addition, a populationbased genetic study in humans showed that pro-ghrelin gene (GHRL) haplotype was associated with sucrose preference (Landgren et al 2011).…”
Section: Discussionmentioning
confidence: 99%